Desenvolvimento de processo utilizando fermentação lática e agentes prebióticos para elaboração de novos tipos de cracker e biscoitos funcionais - Silva, Evaldo Carlos da (2012)
Cookies are products obtained by mixing flour, starch, fat, sugar and other ingredients, undergo the process of kneading and baking, fermented or not. These products are used in food, where the news and functional foods have been gaining market share and consumer preference. For preparation of cracker type cookies are used in the conventional yeast Sacharomyces cereviseae as yeast. In order to introduce innovations and improvements in the quality of the biscuits, were held the following studies: 1) selection and microbiological, biochemical and molecular identification of lactic acid bacteria isolated from wheat flour, starch and fermented milk, 2) the incorporation of lact fermentation in the preparation of crackers instead of general purpose yeast, 3) design of the new industrial process for the preparation of the inoculums, determination of time, fermentation temperatures and pH adjustment, 4) use of inulin and pumpkim fiber for production of cookies with new features and functional properties, 5) study of functional properties and stability of products, analysis of flavor, increase volume, uniformity of structure, formation of alveoli and improvements in the ability of fracture characteristics influenced by this type of fermentation, treatment and presence of the agents used prebiotics, 6) sensory analysis to determine acceptability by consumers. The use of lactc acid fermentation has introduced many advantages over the traditional process, giving characteristics of acceptance and cost savings when compared to the usual process that uses yeast as yeast. Regarding the use of agents injected in fiber, inulin, pumpkim fiber and sensory characteristics to the offered new cookies with cocts compatible with the market.